Developing an evidence based school accountability framework - Purse, Christopher Kenneth; University of Lethbridge. Faculty of Education (Lethbridge, Alta. : University of Lethbridge, Faculty of Education, 2000, 2000)
xi, 127 leaves 29 cm. -- The goal of this project was to develop a new method of assessing school accountability. The project arose from dissatisfaction with a mandated model of externally driven school reviews. The external process involved a week-long survey of a school. Considerable emphasis was placed on generating a review report, but there seemed to be little emphasis on actually working toward improving schools by acting on the report recommendations. A significant shortcoming of the external review process is the lack of interest on the part of the staff being reviewed. The challenge became to develop a process that involves the staff in the entire evaluation process. Based on the notion that one of the most effective forms of evaluation is accomplished through the collection of tangible evidence, the project delves into an examination of demonstrating accountability through the collection of evidence. A number of topics were reviewed in the educational literature in order to develop a philosophy for this process. The next step was to take tasks from my job description and collect evidence to demonstrate how I performed in my own accountability framework. This gave me valuable experience with the process of documenting accountability. My conclusion is that this is a worthwhile task as, based on ajob description, anyone can determine what is actually being done and what needs more attention. In the case of a school system, the starting point is the Education Act. Typically included in Education Acts are statements of the legal duties of school staff, which provide the basis for the operation of schools. The statements in the Northwest Territories Education Act were analyzed and grouped into themes to develop the items for this school accountability framework. This project stops at the frramework development stage, but provides some direction for future steps to complete the process. Prior to use in the schools, the framework will need to be harmonized with the Nunavut Education Act which is currently ...